Violence Against Women and Girls Resource Guide : Agriculture Sector Brief - World Bank (Washington, DC, 2022)
Women and girls play a key role in agriculture and food systems. Globally, women and girls play an important role in the agricultural labor force across the globe. In addition, women tend to have a predominant role at the household level related to food security. In this context, integrating measures to prevent and respond to Violence Against Women and Girls (VAWG) into food and agriculture projects is urgent. The aim of the brief is to provide an overview and avenues for actions that are to be identified and understood as effective entry points for practitioners and policy makers in addressing VAWG through agriculture operations. This brief provides guidance on ethics and safety, resources for carrying out a rapid situation analysis, specific and actionable ideas for the implementation of effective interventions at the institutional, sectoral, and community levels, detailed examples of promising practices, key areas for integrating VAWG prevention and response by key agriculture and food project sub-sector, a menu of indicators for use in monitoring and evaluation, and dozens of active links to more detailed resources and toolkits.